2010
DOI: 10.1007/s10865-010-9287-3
|View full text |Cite
|
Sign up to set email alerts
|

Short sleep mediates the association between long work hours and increased body mass index

Abstract: This study examined whether short sleep duration, physical activity and time spent sitting each day mediated the association between long work hours and body mass index (BMI). Participants included 16,951 middle aged Australian adults who were employed in full time work (i.e. ≥35 h a week). Data on BMI, sleep duration, work hours and other health and demographic variables were obtained through a self-report questionnaire. A multiple mediation model was tested whereby sleep duration, physical activity and amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 47 publications
0
28
1
2
Order By: Relevance
“…2,5 In fact, several studies have indicated that the linkage between longer work hours and obesity is mediated by shorter sleep duration. [39][40][41] Interestingly, the younger drivers in our sample had higher odds for being overweight, obese, or extreme obese, which went against our hypothesis, but the review by Solovieva et al 17 also found that younger male workers were more likely to gain weight with increased work hours than older workers. With 70% of our sample working on average more than 11 hours daily (or an estimated 55 to 70 hours per week), this is comparable to Sieber et al's 20 findings of approximately 60 hours of weekly work among their national survey of US drivers.…”
Section: Discussioncontrasting
confidence: 66%
“…2,5 In fact, several studies have indicated that the linkage between longer work hours and obesity is mediated by shorter sleep duration. [39][40][41] Interestingly, the younger drivers in our sample had higher odds for being overweight, obese, or extreme obese, which went against our hypothesis, but the review by Solovieva et al 17 also found that younger male workers were more likely to gain weight with increased work hours than older workers. With 70% of our sample working on average more than 11 hours daily (or an estimated 55 to 70 hours per week), this is comparable to Sieber et al's 20 findings of approximately 60 hours of weekly work among their national survey of US drivers.…”
Section: Discussioncontrasting
confidence: 66%
“…Psychosocial factors at work and long work hours might increase the frequency of eating higher caloric value food (44), decrease physical activity (45), and reduce sleep (46,93). They may also increase the risk of weight gain and obesity directly through neuroendocrine pathways (40).…”
Section: Discussionmentioning
confidence: 99%
“…Long work hours might interfere with various activities including sleep 12) , and disruption of the circadian rhythm could play a role in the development of metabolic problems such as obesity 24) . Magee et al 14) reported that long work hours were indirectly associated with high body mass index, and short sleep might mediate this association. Short sleep could also be associated with the changes in hormone levels such as leptin and ghrelin, which play an important role in the regulation of energy storage and the sense of hunger and satiety in the human body 25) .…”
Section: Discussionmentioning
confidence: 99%
“…Work-related factors such as work hours 12) and shift work 13) are also related to obesity. Long work hours might lead to weight gain through lack of exercise, undesirable eating habits, and reduced sleep hours 12,14) . The presence of gender differences in the association between work hours and obesity is controversial.…”
mentioning
confidence: 99%